Comparative Analysis Of The Thoughts Of Umer Chapra And Dawam Rahardjo In Syariah Banking - lukmanul hakim; A.M. Fadli Dzil Jalal Dzil Jalal (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
This research aims to compare two Islamic economists, namely Umer Chapra and Dawam Rahardjo, regarding Islamic banking, which includes its goals, principles, and systems. The method used in this research is the literature study method; besides that, this research also uses a comparison method between two Islamic economists, namely Umer Chapra and Dawam Rahardjo. The results of this study indicate differences and principles of thought between Umer Chapra and Dawam Rahardjo; Umer Chapra disapproves of the use of riba in the banking process because there is a legal basis for prohibiting riba in the Qur'an. This is different from Dawam Rahardjo's view in principle; several conditions allow excess borrowing of money or riba due to a decrease in the value of the currency so that the value in the past is not comparable to the value of money in the future (inflation theory) so that additional funds are needed to cover losses arising from the decline in the value of money. Regarding the principles of Islamic economic development, these two figures have the same thoughts related to recommended economic development cooperation, such as using the zakat, alms, and waqf methods, and have the same thoughts regarding Islamic banking in terms of management. Also, there is support related to implementing sharia-based banking in Indonesia.